Management of ventriculoperitoneal shunt complications in children: A review of 34 cases - Rajendra Kumar Ghritlaharey (Wolters Kluwer Medknow Publications, 2023)
Objectives: The primary objective of this study was to analyse the demographics of the children who presented with ventriculoperitoneal shunt (VPS) complications. The secondary objectives were to review the clinical characteristics, surgical procedures performed for the management of VPS complications and the final outcome. Materials and Methods: This is a single-institution observational study that included children below 12 years of age who required VPS revisions during the study period. Results: During the study period of 10 years, n = 336 VPS catheters were implanted for the treatment of hydrocephalus in children. Forty (11.90%) children developed various VPS complications and required VPS revisions in the follow-up period. A total of n = 30 (8.92%) children (n = 21 boys and n = 9 girls) were selected/recruited for the present study, and they required n = 34 revision procedures. The mean interval from VPS insertion to the diagnosis of the complication was 7.29 months. VPS complications that required revisions occurred in the following order of frequency: (1) VPS catheter, cerebrospinal fluid (CSF) or shunt tract infection n = 8 (2.38%); (2) malfunction of distal VPS catheter n = 7 (2.08%); (3) coiling of distal VPS catheter at abdominal area n = 6 (1.78%); (4) extrusion of VPS catheter n = 5 (1.48%); (5) CSF leak from abdominal wound site/umbilicus n = 4 (1.19%); (6) malfunction of ventricular catheter n = 3 (0.89%) and (7) CSF pseudocyst peritoneal cavity n = 1 (0.29%). Surgical procedures were performed for the treatment of abovementioned complications in the following order of frequency: (1) revision of distal VPS catheter n = 14 (4.16%), (2) removal of entire VPS catheter ± external ventricular drainage (EVD) n = 7 (2.08%), (3) distal VPS catheter converted as EVD n = 6 (1.78%), (4) revision of proximal VPS catheter n = 3 (0.89%), (5) revision of entire VPS catheter n = 3 (0.89%) and (6) CSF pseudocyst excision n = 1 (0.29%). This study also documented n = 2 (6.6%) deaths during the post-operative period. Conclusion: VPS insertion done for the treatment of hydrocephalus in infants and children was associated with various complications. Seventy per cent of the complications occurred within the first 6 months after the VPS insertion. Two-thirds of the complications were related to the distal VPS catheter.